Analisis Likuiditas Pada PT Bank Danamon Tbk - Halik, Maria Yessica; Todingbua, Manuel August; Watilette, Litha Clara; Somalinggi, Edgberth (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2023)
This research was conducted at PT Bank Danamon Tbk. aims to analyze the development of liquidity from financial ratios. The research method used in this research is ratio analysis method. After conducting research on PT Bank Danamon Tbk by calculating financial ratios based on bank liquidity formulas, namely the Qiuck Ratio, Cach Ratio, and LDR from the calculation of the results for the period 2019 to 2021, the following results are obtained: according to the liquidity ratio, it can be seen that banks can meet their financial obligations properly. This is proven by the Quick Ratio and Cash ratio values ​​which have exceeded the normal standard set by Bank Indonesia, where the normal standard is >4.05%. The finding of the LDR ratio of PT Bank Danamon Tbk was 117.56% in 2019, 108.68% in 2020, and 111.3% experienced unhealthy conditions because it exceeded that determined by Bank Indonesia above> 94%.